2007
DOI: 10.1007/s15010-007-6169-x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Genotypic Resistance Mutations in Chronic HIV-1 Treated Individuals After Completion of the National Access to Antiretroviral Program in Thailand

Abstract: With the increased availability of antiretroviral therapy in a resource-constrained country, antiretroviral drug resistance should be closely monitored. HIV-1 drug resistance testing to enable the salvage therapy will remain a priority in Thailand. Furthermore, resistance testing should also become routine before prescribing treatment, and the consequences of continuing to provide a failing regimen must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Second are data to support a potential risk-based, prioritized approach to baseline ARV-DR testing among ARV drug-naïve, recently infected HIV patients who report a sexual partner with ARV non-adherence or GPO-VIR treatment failure. While the temporal rise in ARV-DR was not statistically significant, the trend is consistent with a short list of observational studies from Thailand that have characterized the emergence of ARV-DR among persons with ARV experience and treatment failure despite a universal ARV access programme [11][12]. Together, these surveillance and cohort studies suggest that additional system-, provider-and patient-level support is needed to secure ARV drug delivery and minimize the emergence of ARV-DR.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Second are data to support a potential risk-based, prioritized approach to baseline ARV-DR testing among ARV drug-naïve, recently infected HIV patients who report a sexual partner with ARV non-adherence or GPO-VIR treatment failure. While the temporal rise in ARV-DR was not statistically significant, the trend is consistent with a short list of observational studies from Thailand that have characterized the emergence of ARV-DR among persons with ARV experience and treatment failure despite a universal ARV access programme [11][12]. Together, these surveillance and cohort studies suggest that additional system-, provider-and patient-level support is needed to secure ARV drug delivery and minimize the emergence of ARV-DR.…”
Section: Discussionsupporting
confidence: 79%
“…Together, these surveillance and cohort studies suggest that additional system-, provider-and patient-level support is needed to secure ARV drug delivery and minimize the emergence of ARV-DR. The prior studies in ARV-experienced patients have identified the need for national surveillance for baseline ARV resistance among HIV drug-naïve patients, while generic NNRTI-based regimens (GPO-VIR) remain first-line treatment and recommendations for resistance testing are selective [11][12]. While our data do not support routine ARV-DR testing among all ARV-naïve patients in Thailand, our findings suggest that baseline ARV-DR may be justified in newly diagnosed patients with HIV infection who identify an ARV-experienced, HIV-infected sexual partner who acknowledges ARV non-adherence or treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the connection of the Thai HIV-1 epidemic with other epidemics in the region, through travel and trafficking of drugs and persons, has been reflected in the genetic relatedness of Thai strains to those from other countries in the Golden Triangle (i.e., a major illicit opium-producing area spanning Myanmar [Burma], Vietnam, Laos, and Thailand) (34,35) and China (36). Subtypes A, C, D, and CRF02_AG-which are more common in African epidemics-have been detected sporadically (37)(38)(39); however, to date there have been no indications that these strains have spread locally.…”
mentioning
confidence: 99%
“…This finding might discourage the use of EFdA as a first-line therapy, because it might preclude 3TC and FTC from subsequent use in these patients. However, M184I/V mutations are already prevalent in treatment-experienced patients due to the widespread use of both 3TC and FTC in HAART (20,25). Indeed, despite the appearance of M184V/I-containing variants in the rebounded virus after drug was removed, EFdA successfully controlled virus burden to undetectable levels in both blood and tissues throughout the interval of therapy.…”
Section: Discussionmentioning
confidence: 99%